2002
DOI: 10.1001/archopht.120.11.1509
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Visual Field Defects on Driving Performance

Abstract: To investigate the effect of visual field defects on driving performance, and to predict practical fitness to drive. Methods: The driving performance of 87 subjects with visual field defects due to ocular abnormalities was assessed on a driving simulator and during an on-road driving test. Outcome Measures: The final score on the on-road driving test and simulator indexes, such as driving speed, viewing behavior, lateral position, time-headway, and time to collision. Results: Subjects with visual field defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 16 publications
12
121
3
3
Order By: Relevance
“…By comparison, in an on-road study of drivers with more restricted peripheral fields than the range in this study (mean 84° ± 35°compared to 123° ± 20° here), only 43% passed a test of practical fitness to drive (Coeckelbergh et al, 2002). As previously reported for drivers with a diagnosis of glaucoma (McGwin et al, 2004), drivers in the current study appeared to be aware of their visual limitations and self-regulated their driving accordingly; those with more restricted fields drove to fewer places (Figure 1c).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…By comparison, in an on-road study of drivers with more restricted peripheral fields than the range in this study (mean 84° ± 35°compared to 123° ± 20° here), only 43% passed a test of practical fitness to drive (Coeckelbergh et al, 2002). As previously reported for drivers with a diagnosis of glaucoma (McGwin et al, 2004), drivers in the current study appeared to be aware of their visual limitations and self-regulated their driving accordingly; those with more restricted fields drove to fewer places (Figure 1c).…”
Section: Discussioncontrasting
confidence: 61%
“…However, our results suggest that vertical field extent may also be an important consideration, especially in turning or curve-taking maneuvers. Previous studies, which have reported an effect of peripheral visual field restriction on driving performance, have either used simulations of severe visual field restrictions on a closed course (Wood et al, 1993;Wood & Troutbeck, 1992, 1995, or have carried out driving simulator evaluations using patients with more restricted fields than the sample in this study (Coeckelbergh et al, 2002;Szlyk et al, 1992). The only study with a similar range of mild to moderately restricted horizontal field extents (130° ± 21°, range 70° -140°) (Szlyk et al, 2002) failed to find any significant correlations between binocular field width and driving performance in a driving simulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with visual field defects have been tested before in simulated and real driving settings: Bowers et al 12 and Cockelbergh et al 13 carried out studies in a driving simulator and demonstrated poorer driving performance in patients compared to healthy controls. However they did not record eye-and head-movements and individual differences could not be related to visual exploratory behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the real world, however, they may be able to compensate for the loss by exploring the affected (blind) side using head-and eye-scanning. It has been reported that in Holland (where driving with hemianopia is permitted), driving examiners consider increased head-scanning (especially on approach to intersections) to be an effective compensation for peripheral visual field defects (Coeckelbergh et al, 2002). Whether increased head-scanning while driving results in better detection performance has never been quantitatively investigated.…”
Section: Paper Not Available Abstract Objectivesmentioning
confidence: 99%